Efficient Peer-to-peer File Sharing in 3G Networks - 王凯 李建华 (Shanghai jiao tong da xue xue bao, 2009)
In 3G networks upgraded with high speed packet access （HSPA） technology, the high access bandwidth and advanced mobile devices make it applicable to share large files among mobile users by peer-to-peer applications. To receive files as quickly as possible is essential for mobile users in file sharing applications, since they are subject to unstable signal strength and battery failures. While many researches present peer-to-peer file sharing architectures in mobile environments, few works focus on decreasing the time spent in disseminating files among users. In this paper, we present an efficient peer-to-peer file sharing design for HSPA networks called efficient file sharing （EFS） for 3G networks. EFS can decrease the dissemination time by efficiently utilizing the upstream-bandwidth of mobile nodes. It uses an adaptive rearrangement of a node＇s concurrent uploading transfers, which causes the count of the node＇s concurrent uploading transfers to lower while ensuring that the node＇s upstream-bandwidth can be efficiently utilized. Our simulations show that, EFS achieves much less dissemination time than other protocols including Bullet Prime and a direct implementation of BitTorrent for mobile environments.